PROSTATITIS DIAGNOSTIC AND TREATMENT SCHEMES - Toshev S.U.; Rafikova M.F.; Isaev X.D. (PEDAGOGS, 2024)
Annotation: this article attempts to reveal the main causes of chronic urethrogenic prostatitis (CUP) in young men against the background of complex treatment with the use of general and local ozone therapy, depending on the somatic type. To carry out scientific work, the author conducted a study of 306 Caucasian males of the first period of adulthood suffering from CUP. A comprehensive diagnostic program, in addition to standard studies, included: filling out questionnaires for a summary assessment of CUP symptoms and a formula for sexual male function, bacterioscopic, bacteriological and molecular biological studies of urethral discharge and prostate secretion for STIs. The problem in question is still little studied, therefore, requires more thorough research.